Statins in Hepatitis B or C Patients Is Associated With Reduced Hepatocellular Carcinoma Risk: A Systematic Review and Meta-Analysis - Li, Zhiguo; Li, Ying; Li, Xiaoke; Zhang, Ludan; Zhao, Nanqi; Du, Hongbo; Zhou, Bo; Ye, Yong’an (Turkish Journal of Gastroenterology, 2022)
Background: Hepatocellular carcinoma is the world’s leading cause of cancer-related death. Chronic hepatitis B virus and hepatitis C virus infection cause liver cancer. The aim of this study was to investigate the relationship between statins and the risk of hepatocellular carcinoma in patients with hepatitis B or C. Methods: We systematically searched Web of Science, Embase, PubMed, Cochrane Library, China National Knowledge Infrastructure, and Wanfang Database from their inception to January 2019. We included studies that reported the hepatocellular carcinoma incidence among hepatitis B virus- or hepatitis C virus-infected patients or hepatitis B virus- or hepatitis C virus-related cirrhotic patients, evaluated and clearly defined exposure to statins, provided effective comparison groups, and reported risk estimates. Inclusion was not otherwise restricted. Summary relative risk estimates with 95% CIs were calculated using a random-effects model. Results: Meta-analysis of 10 studies showed that statin users had a significantly lower risk of hepatocellular carcinoma (relative risk = 0.47, 95% CI = 0.38-0.56) with significant heterogeneity. In 7 hepatitis studies, using statin was associated with a 53% reduction in the incidence of hepatocellular carcinoma (relative risk = 0.47, 95% CI = 0.43-0.50) with substantial heterogeneity. In 3 cirrhosis studies, the incidence of hepatocellular carcinoma in statin users was significantly reduced by 55% (relative risk = 0.45, 95% CI = 0.30-0.61) with no heterogeneity. Conclusion: Statins reduce the hepatocellular carcinoma risk among patients infected with hepatitis B virus or hepatitis C virus. This chemoprotective association is more pronounced in hepatitis B virus or hepatitis C virus-associated cirrhotic patients. Cite this article as: Li Z, Li Y, Li X, et al. Statins in hepatitis B or C patients is associated with reduced hepatocellular carcinoma risk: A systematic review and meta-analysis. Turk J Gastroenterol. 2022;33(2):136-144.